ANALISIS IMPLEMENTASI MUTU PEMBELAJARAN DI SMP MUHAMMADIYAH 3 BANDAR LAMPUNG - Ikbal, Taufik; kusuma, Nurhadi; Purwanti, Eri (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2018)
AbstractThis study is a study using Roesman's theory approach in the book of learning models to develop teacher professionalism. To measure the extent to which the implementation of learning is considered qualified.From the results of observations and interviews and reviewed from the theory of learning models Roesman then obtained: 1. Bahwasannya in the planning phase of teacher learning in smp muhamadiyah 3 bandar still exist that have not yet compiled syllabus and RPP. 2. In the implementation stage of learning, teachers still have not applied apersepsi in starting learning and have not used props, 3. There are sub indicators in syllabus or indikaator that have not been implemented in each learning subject, 4. At the time of closing the learning and giving assessment of the teacher have been seeking the fulfillment of assessment in accordance with PP Education Minister No 23 of 2016.